Pengaruh Karakteristik Individu, Iklim Organisasi, Disiplin Kerja Terhadap Kinerja Pegawai Dengan Variabel Intervening Motivasi Kerja - Runtulalo, Betrics Traci (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The result of research indicates that 1) individual characteristic variable have positive and significant influence to work motivation 2) organizational climate variable have negative and insignificant influence to work motivation 3) work discipline variable have positive and significant influence to work motivation 4) individual characteristic variable have negative and insignificant influence to employee performance, 5) organizational climate variable have positive and insignificant influence on employee performance, 6) work discipline variable have positive and significant influence to employee performance, 7) work motivation variable has positive and significant influence to employee performance.Keywords: Individual Characteristics, Organizational Climate, Work Discipline, Work Motivation, Employee Performance